Penerapan Digital Marketing sebagai Komunikasi Pemasaran Jasa Photography Happy Stories Terhadap Konsumen di Medan - Naufhal Nabhan; Suheri Harahap; Muhammad Faishal (Communication & Social Media, 2021)
This article discusses how to apply digital marketing as a marketing communication for Happy Storiesphotography services to consumers in Medan. Happy Storiesis a vendor that offers complete photo products and services. Happy Storiesutilizes Instagram as a medium to market its products and services. This article uses descriptive qualitative research methods. Sources of data were obtained from interviews with Happy Storiesowners and two consumers who had used Happy Storiesphotography services. The results of the study show that the application of digital marketing from Happy Storiesuses a very good application of social media marketing. Marketing through digital marketing is able to promote and even create products and services from Happy Stories. Currently, Happy Storiesproducts and services are widely used to capture various moments of activity such as wedding receptions, graduations.